Worker laying in leafcutter ant Acromyrmex subterraneus brunneus (Formicidae, Attini) - Camargo, Roberto S.; Forti, Luiz Carlos [UNESP]; Lopes, Juliane F. S.; Noronha, Newton C.; Ottati, Angelo L. T. (Wiley-Blackwell, 2007)
We studied the process of offspring production in queenless colonies of Acromyrmex subterraneus brunneus, and particularly evaluated the ovary development of workers as a function of their age. For this, subcolonies were set up and evaluated at different periods of isolation from the queen (2, 4 and 6 months), besides individually labeled age groups. The subcolonies were assessed according to offspring production and ovaries containing oocytes or not. The evaluations showed worker oviposition and development of males originating from worker-laid eggs. At 2 months'absence of the queen, eggs and larvae were found, with eggs in a higher proportion than larvae. After 4 months, the proportion of eggs had reduced while larvae had increased, and a pupa was found in one subcolony. At 6 months, besides a higher share of larvae, one pupa and one adult male were found. Dissection of workers revealed ovaries containing oocytes during the periods of evaluation. Only a group of medium-sized and large workers, 23.3%, 20.9% and 37.5% of the population from each period assessed in queenless subcolonies respectively, presented developed oocytes in the ovary. The same was observed in colonies with a queen, with 17.6%, 19.6% and 7.8% of the group of dissected workers from each time period, respectively. With respect to worker age, we observed by dissection of the ovary, that the greatest percentage of individuals with ovarioles containing oocytes occurred at 45 days (6 weeks) up to 90 days (12 weeks). These results probably are associated with the workers reproduction and the laying of trophic and reproductive eggs in colonies with and without a queen; these eggs have distinct functions in each situation.
Keywords: leafcutter ant; queenless ant colonies; reproduction conflict; worker laying; worker reproduction